The Role of Universities in Research and Technology Transfer to Improve Livelihoods in Southern Africa - Moalosi, W. T. S.; Mogapi, M.; Ahmad, Jamil (Advances in Social Sciences Research Journal, 2017)
Every country in Southern Africa has well-regarded universities where expert researchers work in a wide array of disciplines. Yet, not far from these campuses rural poor might be living whose lives could be dramatically transformed if the universities used some of its expertise to develop and transfer appropriate technology to such communities. Since the gap in knowledge of modern science and technology between experts in universities and the poor communities is so vast, a programme of developing and transferring appropriate technology could be a game changer for rural communities. Areas of need could be identified by forming multidisciplinary teams comprising specialists in adult education, social scientists, engineers, architects, agriculturists, community medicine specialists, environmental scientists and public health experts among others. Some areas where appropriate technology transfer may be relevant depending on the community and the available expertise are solar energy, biogas, water harvesting and conservation, communications, animal husbandry, arid agriculture and horticulture, tourism, housing and cottage industry. Some of this work is already taking place, but we emphasize a multi-disciplinary approach where social scientists, educationists, financial experts and marketing specialists (for cottage industry) work side by side with scientists and technologists. Key words: Multidisciplinary, technology transfer, research, livelihoods, rural communities, extension.